Fast flex: Strategic design for industrial real estate in the age of corporate agility. (April 2019) - Sternberg, Ernest; LiPuma, V. Jeffrey; Warren, Harry
In view of global hypercompetition and technological change, the strategic management literature observes a shift away from competitiveness based on long-term competence to that based on flexibility. As corporations adopt strategies of corporate agility in production and distribution, they often respond by divesting themselves of fixed landholdings. They increasingly outsource their space needs to real estate developers who act as space providers. While this trend occurs in both office and industrial properties, it is less understood in the latter. Industrial land developers must now quickly ("fast") adjust properties to fulfill the corporate clients' demand for flexibility ("flex"). Sites, physical structures, and contracts have to be designed to foster rapid transition from one occupant and building configuration to another and to serve multiple submarkets and client preferences.